UNMET NEED OF HEALTH FACILITIES IN BOGOR REGENCY - Adhitya Kusuma Wahyunugroho (Poltekkes Kemenkes Semarang, 2020)
The existence of health facilities (fasilitas kesehatan/faskes) especially at the district level is considered very appropriate to reduce the number of people whose health is impaired. For this reason, a targeted program needed to reduce this number. The program is by reducing the number of unmet needs in areas that have high population, high rate of increase and high density. This is very in accordance with the characteristics of Bogor regency as a research locus. The method used in this research is a combination method, which is a combination of tabular analysis (statistics) with spatial data. The combination of the two will produce locations with low unmet need health facilities resulting from a causality of 2 (two) variables, both of these variables are the number of residents with the number of health facilities, so that the precise and accurate results will be obtained. The conclusion from the spatial analysis is that there are 19 from 40 sub-districts in Bogor regency whose indicators of unmet need for low health facilities. Although this research is considered very simple, the results of this study are very important because it can be used as a guideline for the development of health facilities, especially community health centers (Puskesmas) in Bogor regency.